1988
DOI: 10.1021/jm00399a016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiulcer activity of 5,11-dihydro[1]benzoxepino[3,4-b]pyridines

Abstract: A series of substituted 5,11-dihydro[1]benzoxepino[3,4-b]pyridines was synthesized and evaluated for antiulcer activity in water immersion/restrained stress ulcer assay in rats. Structure-activity relationships are described. Most of the tested compounds exhibited low affinity to the muscarinic acetylcholine receptor. The molecular features for the best activities are the 2-(diethylamino)ethylenediamine group at the 5-position of the oxepin ring and an oxepin skeleton rather than a thiepin or a pyran skeleton.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…reported to be effective in the treatment of gastroduo denal ulcers by their antisecretory action mediated through blockade of muscarinic receptors or histamine H2-receptors and uptake inhibition of noradrenaline or serotonin (3,4,28,29). KW-5805, however, has a very weak musucarinic receptor binding (1/30 of pirenzepine) (13) and no effect on H2-receptors and noradrenaline up take (A. Ishii et al, unpublished data). The mode of the antisecretory action of KW-5805 is thus apparently differ ent from those of cimetidine and tricyclic antidepressants and may be mediated at least partly through its weak an timuscarinic action as compared to pirenzepine.…”
Section: Discussionmentioning
confidence: 99%
“…reported to be effective in the treatment of gastroduo denal ulcers by their antisecretory action mediated through blockade of muscarinic receptors or histamine H2-receptors and uptake inhibition of noradrenaline or serotonin (3,4,28,29). KW-5805, however, has a very weak musucarinic receptor binding (1/30 of pirenzepine) (13) and no effect on H2-receptors and noradrenaline up take (A. Ishii et al, unpublished data). The mode of the antisecretory action of KW-5805 is thus apparently differ ent from those of cimetidine and tricyclic antidepressants and may be mediated at least partly through its weak an timuscarinic action as compared to pirenzepine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that KW-5805 is an antiulcerogenic compound that acts on the defensive mechanisms (3), as its antisecre tory activity is weak in pylorus-ligated rats (1,2). However, the present results indicate that KW-5805 could inhibit gastric acid secretion through centrally mediated mecha nisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its affinity to the muscarinic receptor was low as compared with that of pirenzepine in the receptor binding assay (1). This compound showed weak antisecretory activity after i.d.…”
Section: -[2-(diethylamino)ethyl]aminomentioning
confidence: 90%
See 2 more Smart Citations